STRATEGI POLA ASUH BERPENDEKATAN TRI KAYA PARISUDHA SEBAGAI SUATU LAYANAN BIMBINGAN SISWA SEKOLAH DASAR - Ketut Ngurah Ardiawan; Luh Padmadewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Education in Indonesia at this time needs to be considered thoroughly especially inobserving various students’ behaviours and actions which currently lead to a lot of undesirableevents. Many students bully, insult, mock, fight and even slander their friends because of the lowvalue of the character applied to themselves both at home and at school. Teachers at schools inguiding students need to apply a parenting style, in this case, parenting is the way of educating,caring, treating and understanding students so as to shape student personality for the bettercharacteristics. With a parenting strategy approaching Tri Kaya Parisudha, of course, the threeactions/behaviors that must be purified with its parts which are thinking, saying and doing gooddeeds, it will bring peace in human life. The teacher must apply the concept of the teaching inhimself first and also apply it towards the student about the concept so that students will be ableto control thoughts that will lead to good words and deeds.